MANAGEMENT OF LOCAL ANAESTHESIA FOR DENTAL PROCEDURES IN HYPERTENSIVE PATIENTS: A REVIEW OF THE LITERATURE - Fatkhurrohman, Fuad; Sukmawardani, Anissa; Rohmah, Mufidatul (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Hypertension is a major global health issue with a high prevalence and is often a risk factor for various cardiovascular complications such as coronary artery disease, stroke, and heart failure. Hypertensive patients who are uncontrolled or have other comorbidities tend to be more susceptible to hemodynamic changes during induction, maintenance, and recovery from anesthesia. Method: The materials and methods of this study were derived from various literatures regarding anesthesia in hypertensive patients. The literature was obtained from journals, sourced from Google Scholar. The articles were from the years 2021 to 2024. Result: Optimal blood pressure control before the procedure is crucial to prevent serious complications, such as stroke or myocardial infarction. During anesthesia induction, the choice of anesthetic agents must be tailored to the patient's condition to avoid excessive blood pressure reduction, and close monitoring should be performed throughout the procedure. After surgery, it is important to continue careful blood pressure management and ensure safe recovery to prevent long-term negative health impacts on hypertensive patients.